1992
DOI: 10.1029/92wr01366
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning solute transport between infiltration and overland flow under rainfall

Abstract: Solute transport from soil to overland flow is an important source of nonpoint pollution and was investigated through tracer studies in the laboratory and at an outdoor laboratory catchment. The depth of surface water interaction with soil, defined as the mixing zone is a useful value for approximate estimation of potential solute transport into surface water under rainfall. It was measured in the laboratory for a noninfiltration case (0.90 to 1.0 cm) and estimated through mass balance modeling for an infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 22 publications
(3 reference statements)
1
34
0
Order By: Relevance
“…Various hypotheses have been invoked to explain possible factors that affect the migration and distribution of solutes under unsaturated, heterogeneous conditions, including turbulent mixing due to high rainfall (Havis et al, 1992); solute transfer between mobile and immobile water (De Smedt and Wierenga, 1984); mobile-immobile exchange and hysteresis (Butters et al, 1989;Russo et al, 1989aRusso et al, , b, 2014; lateral mixing due to velocity fluctuations (Russo et al, 1998); isotope effects (Barnes and Allison, 1988;LaBolle et al, 2008;Zhang et al, 2009);variable, state-dependent anisotropy (McCord et al, 1991); non-Gaussian early-time mean tracer plume behavior (Naff, 1990); non-Fickian solute migration at low water contents (Padilla et al, 1999) and for macroscopically homogeneous sand (Bromly and Hinz, 2004); and saturation-dependent dispersivity (Raoof and Hassanizadeh, 2013). In addition, Konikow et al (1997) and Parker and van Genuchten (1984) discuss the importance of boundary condition treatment (e.g., water-solute injection, solute exchange between soil and atmosphere).…”
Section: Discussionmentioning
confidence: 99%
“…Various hypotheses have been invoked to explain possible factors that affect the migration and distribution of solutes under unsaturated, heterogeneous conditions, including turbulent mixing due to high rainfall (Havis et al, 1992); solute transfer between mobile and immobile water (De Smedt and Wierenga, 1984); mobile-immobile exchange and hysteresis (Butters et al, 1989;Russo et al, 1989aRusso et al, , b, 2014; lateral mixing due to velocity fluctuations (Russo et al, 1998); isotope effects (Barnes and Allison, 1988;LaBolle et al, 2008;Zhang et al, 2009);variable, state-dependent anisotropy (McCord et al, 1991); non-Gaussian early-time mean tracer plume behavior (Naff, 1990); non-Fickian solute migration at low water contents (Padilla et al, 1999) and for macroscopically homogeneous sand (Bromly and Hinz, 2004); and saturation-dependent dispersivity (Raoof and Hassanizadeh, 2013). In addition, Konikow et al (1997) and Parker and van Genuchten (1984) discuss the importance of boundary condition treatment (e.g., water-solute injection, solute exchange between soil and atmosphere).…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous research (e.g. Hubbard et al, 1989a,b;Havis et al, 1992) as well as the results of trial 7, site 4 ( Figure 5g) have shown that the shape, as well as the position of the curve, changes with changes in y i . If runo occurs during the early stages of in®ltration then there is potential for a very high initial Br concentration in the runo.…”
Section: Use Of Constant a And Bmentioning
confidence: 74%
“…14, 1139±1158 (2000) where C p is the concentration of the chemical in precipitation (mg l À1 ), C r is the concentration of the chemical in surface water (mg l À1 ), C s is the concentration of the chemical in soil solution (mg l À1 ), f is the in®ltration rate (m s À1 ), q is the¯ow in the x direction per unit width (m 2 s À1 ), R is the rainfall rate (m s À1 ), t is time (s), x is the distance in the direction of horizontal¯ow (m), y is surface water depth (m) and a is the mass transfer coecient (m s À1 ). Equation (4) has similarities with the mass balance equations for the lateral transport of dissolved chemicals by surface runo presented by Havis et al (1992) and Wallach and Shabtai (1992a,b).…”
Section: Chemical Transfermentioning
confidence: 84%
See 1 more Smart Citation
“…He verified the model using a set of published experimental data and concluded that kinematic wave theory was a promising tool for storm water modelling. Havis et al (1992) partitioned solute transport between infiltration and overland flow under rainfall. They concluded that solute transport from soil to overland flow was an important source of non-point pollution.…”
Section: Introductionmentioning
confidence: 99%